2000
DOI: 10.1111/j.1553-2712.2000.tb02248.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Evaluation of Patients with Blunt Abdominal Trauma: A Decision Analysis

Abstract: Abstract. Objectives: Using decision analysis, to compare the expected utility (EU) of diagnostic peritoneal lavage (DPL), computed tomography (CT), and ultrasonography (US) to determine the optimal modality for the evaluation of blunt abdominal trauma (BAT) in hemodynamically stable adults. Methods: Data points for the decision analysis were obtained from three sources: 1) prevalence of BAT and the sensitivity and specificity of each diagnostic modality were determined through a criteria-based review of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Clinical examination has been found to be the corner stone for primary assessment of blunt abdominal trauma patients. 9 In this study, author found abdominal distension and tenderness to be the most common positive findings in about 75% cases which was consistent with the existent literature. 10 In this study the most common grades of splenic injury were Grade II and III (According to AAST grading system on CECT abdomen) comprising 70% of the patients.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical examination has been found to be the corner stone for primary assessment of blunt abdominal trauma patients. 9 In this study, author found abdominal distension and tenderness to be the most common positive findings in about 75% cases which was consistent with the existent literature. 10 In this study the most common grades of splenic injury were Grade II and III (According to AAST grading system on CECT abdomen) comprising 70% of the patients.…”
Section: Discussionsupporting
confidence: 90%
“…17 CECT has been used to evaluate the patients of blunt trauma abdomen and found highly specific and sensitive for diagnosing the solid organ injury, the amount of hemoperitoneum, or retroperitoneal traumatic lesions and thus predicting the management option in these patients. [18][19][20][21][22] Increasing success rates have been reported with conservative management of abdominal solid organ injuries after blunt trauma, however, most data are retrospective.…”
Section: Discussionmentioning
confidence: 99%
“…Important factors include information regarding fatalities at the scene, vehicle type and velocity and steering wheel deformity, etc [13]. Physical examination: While some studies cite physical examination as only 55-65% sensitive for BAT, it is still the cornerstone for primary assessment [14]. Injuries involving the respiratory or CVS may take precedence over an abdominal injury [15].…”
Section: Blunt Abdominal Trauma (Bat)mentioning
confidence: 99%